Event-Triggered Distributed State Estimation Under Unknown Parameters and Sensor Saturations Over Wireless Sensor Networks - Basit, Abdul; Tufail, Muhammad; Rehan, Muhammad (IEEE transactions on circuits and systems. II, Express briefs, 2022)
In this brief, the distributed state and parameter estimation problem is addressed for a class of discrete-time nonlinear systems subject to sensor saturations over wireless sensor networks. In this regard, a novel estimation design is proposed that involves identification of an unknown parameter under event-triggering mechanism. A sufficient condition for exponential uniform ultimate boundedness of estimation error is established using Lyapunov stability theory. The estimator gains to ensure boundedness of error are linked to the solution of inequality constraints. Finally, the effectiveness of proposed estimator is demonstrated using a simulation example.